Use of the small punch test for the estimation of ductile-to-brittle transition temperature shift of irradiated steels. (March 2021) - Altstadt, E.; Bergner, F.; Houska, M.
Highlights: Correlations between Charpy-V-based and small-punch-test based ductile-to-brittle transition temperatures. Re-use of samples to gain additional information on the irradiation and annealing behaviour. Comparison of two fitting methods for small-punch-test-based transition temperatures. Abstract: The small punch test is evaluated as a screening procedure for irradiation embrittlement of reactor pressure vessel steels. In particular, the correlation between ductile-to-brittle transition temperatures obtained from this small specimen test technique and from the standard Charpy impact test is investigated. Small punch tests and Charpy impact tests at different temperatures were performed on various steels including materials from original reactor pressure vessels in the unirradiated, neutron irradiated and annealed condition. It is demonstrated that the small punch test is a reliable and effective supportive means for the estimation of the irradiation-induced shift of the ductile-to-brittle transition temperature. It was found that a tanh-fit of the normalized small punch energy in dependence of temperature is preferable in comparison to the two-curve fit of the total small punch energy.